1998
DOI: 10.1209/epl/i1998-00111-0
|View full text |Cite
|
Sign up to set email alerts
|

Midgap states of a two-dimensional antiferromagnetic Mott-insulator: Electronic structure of meron vortices

Abstract: We demonstrate from first principles that ferromagnetic core, meron vortex configurations of the spin-1 2 antiferromagnet in two-dimensions give rise to midgap electronic states in the Mott-Hubbard charge gap. Merons are collective mode excitations of the antiferromagnet and are induced by doping the system with charge carriers. They are the topological analogs of charged bosonic domain wall solitons in one-dimension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…In this nontrivial magnetic structure the Mn and Fe magnetic moments rotate out of the surface plane, around the central Mn site, in a "lotus flower"-like spin configuration that resembles a half-skyrmion, i.e., a meron, topological object. 49,56 It is interesting to note that Heinze et al 57 have reported the existence of a two-dimensional square lattice of skyrmions as the magnetic ground state of an Fe film on Ir(111) surface. The microscopic origin has been explained in terms of a complex interplay between exchange interactions of various orders and Dzyaloshinskii-Moriya interactions.…”
Section: B Mn Nanostructures On Fe(001)mentioning
confidence: 99%
“…In this nontrivial magnetic structure the Mn and Fe magnetic moments rotate out of the surface plane, around the central Mn site, in a "lotus flower"-like spin configuration that resembles a half-skyrmion, i.e., a meron, topological object. 49,56 It is interesting to note that Heinze et al 57 have reported the existence of a two-dimensional square lattice of skyrmions as the magnetic ground state of an Fe film on Ir(111) surface. The microscopic origin has been explained in terms of a complex interplay between exchange interactions of various orders and Dzyaloshinskii-Moriya interactions.…”
Section: B Mn Nanostructures On Fe(001)mentioning
confidence: 99%
“…As a result, the 2D HF equation reduces trivially to a 1D radial equation, with a structure very similar to that of the 1D differential HF equation obtained for the 1D Hubbard model. 17,18 Once this radial 1D solution is found, the 2D configuration is simply generated through a 2π rotation about an axis perpendicular to the 2D plane. As a result, there is a close analogy between solutions obtained for the 1D Hubbard model and for the 2D spin-flux model, in all our investigations.…”
Section: Doping Induced Meron-vortex Solitonsmentioning
confidence: 99%
“…An argument based on the electronic structure, identical to the one offered for the charged bosonic domain-walls of the polyacetylene, also holds. 17,18,14,20 The parallel to the quasi-one dimensional 1D polyacetylene is again a reflection of azimuthal symmetry which reduces the 2D continuum model to a 1D radial equation. Clearly, the isotropic dispersion about the Fermi points is responsible for the appearance of bosonic charge carriers.…”
Section: Doping Induced Meron-vortex Solitonsmentioning
confidence: 99%
See 2 more Smart Citations